If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ax + 7 + -7x + -1a = 0 Reorder the terms: 7 + -1a + -7x + xA = 0 Solving 7 + -1a + -7x + xA = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -1a + -7x + -7 + xA = 0 + -7 Reorder the terms: 7 + -7 + -1a + -7x + xA = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1a + -7x + xA = 0 + -7 -1a + -7x + xA = 0 + -7 Combine like terms: 0 + -7 = -7 -1a + -7x + xA = -7 Add '7x' to each side of the equation. -1a + -7x + 7x + xA = -7 + 7x Combine like terms: -7x + 7x = 0 -1a + 0 + xA = -7 + 7x -1a + xA = -7 + 7x Add '-1xA' to each side of the equation. -1a + xA + -1xA = -7 + 7x + -1xA Combine like terms: xA + -1xA = 0 -1a + 0 = -7 + 7x + -1xA -1a = -7 + 7x + -1xA Divide each side by '-1'. a = 7 + -7x + xA Simplifying a = 7 + -7x + xA
| (9x+2)+(178-9x)=180 | | (9x+2)+(178-9x)-180=0 | | 3(2a-7-a)= | | 24-7x=3y | | 30y+1.20y= | | 20sinx-20cosx=0 | | 160=4x^2+156x | | 6w+15= | | 5a-9=-59 | | X+y+x^2+y^2=40 | | X^3+3x^2+2x=40(x+(x+1)+(x+2)) | | 6(5x-12)=18 | | 3g/g | | y+27=56 | | 53+2x=8x-37 | | (x^3)-(2.25x^2)=-1 | | x^3-2.25x^2=-1 | | (4*8*11)-(8*8)= | | 5x+6y-7=0 | | 2x^2-36=12 | | 3*9/22 | | 10/14*100= | | X-22=Y | | 22-5x=7x+10 | | (x^2+1)*2.25=x^2+1+2.25 | | 6y-4y=-8+2 | | 6b-5a=4 | | f(x)=-3x^2+2x+4 | | 7p+2q=-5 | | 4xln(x)=0 | | 2t+11=34 | | 4s=29 |